Виноваты звезды: [роман] / Джон Грин - Грин Джон (Must Read - Прочесть всем, 2016)
Экземпляры: аб. ЦБ (2017.04.05) / Инвентарный номер: 3131 / Цена: / Сис.шифр: 84 (7Сое) / Авт.знак: Г 85 / ГРНТИ: 17 / ББК: 84(7Сое)